Community-Based Nursing and Public Health: A Synergistic Approach to Health Promotion - Alanazi, Dalal Muteb Mohammed; Alanazi, Munirah Muteb Mohammed; Alanazi, Fawziah Muteb Mohammed; Aldhafiri, Mohammed Tamoush; Albalawi, Dr.Feras Naji Mahmoud; Alanazi, Norah Abdullah M; Alghumayz, Sulaiman Mohammed; Alwani, Sultan Abdulrahman O; Almutairi , Osama Zaid Muassi B; Almusaad, Abdulaziz Saeed (Journal of Ecohumanism, 2024)
Community-based nursing and public health are pivotal in addressing the complex health needs of populations, particularly in underserved and vulnerable communities. This article examines the synergistic relationship between these fields and their collective impact on health promotion. Employing a mixed-methods approach, the study combines qualitative insights from community-based nurses with quantitative analysis of health outcomes in three diverse communities. Results indicate that collaboration between community-based nursing and public health improves health literacy, enhances access to care, and reduces preventable health disparities. Key challenges, such as resource constraints and workforce shortages, are discussed alongside opportunities for leveraging technology and policy support to strengthen these partnerships. The findings underscore the transformative potential of integrating nursing expertise with public health strategies to achieve sustainable health outcomes.